The Effect of Health Education on Knowledge of the Dangers of Smoking in Students of SMK Negeri 4 Yogyakarta - Prisilla Maya Heni Pratiwi; Putri, Rachma Greta Perdana; Sukirto, Novi Wijayanti; Astuti, Fardhiasih Dwi (Universitas Ahmad Dahlan, 2024)
Smoking is the activity of smoking tobacco rolls wrapped in paper or nipa leaves and then burning and producing smoke. In thesurvey results of the Ministry of Health of the Republic of Indonesia, the risk of smoking behavior in junior and senior high school students in Indonesia in 2015 was 32.82% in male students. Smoking habits lead to health risk for cardiovascular and respiratory diseases and many types of cancer. Smokers have moderate knowledge of tobacco. The study's aim is to examine the effect of health education on knowledge of the dangers of smoking in students of SMK Negeri 4 Yogyakarta. This study utilized a pre-experimental design method with One-Group Pretest-Posttest design approach. The study sample consisted of 127 students who met inclusion and exclusion criteria in class X students of SMK Negeri 4 Yogyakarta. The pretest and post-test scores varied from 22 to 29 with increased scores of the post-test’s trend. Statistical analysis using chi-square test analysis showed a p-value of 0.000 (<0.05). These results suggest that there is an influence between health education on knowledge of the dangers of smoking in students of SMK Negeri 4 Yogyakarta